2003
DOI: 10.1111/j.1540-5414.2003.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the End‐User Computing Satisfaction Instrument: Replication within an ERP Domain*

Abstract: Over the past decade, organizations have made significant investments in enterprise resource planning (ERP) systems. The realization of benefits from these investments depends on supporting effective use of information technology (IT) and satisfying IT users. User satisfaction with information systems is one of the most important determinants of the success of those systems. Drawing upon a sample of 407 end users of ERP systems and working within the framework of confirmatory factor analysis (CFA), this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0
23

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 62 publications
(102 reference statements)
4
95
0
23
Order By: Relevance
“…In fact, this model operationalizes customer satisfaction for e-banking as a multidimensional construct, which includes dimensions are content, accuracy, format, ease of use, timeliness and safety (See Figure 2). Notably, this model is rooted from user satisfaction literature, especially previous studies from Doll, Xia and Torkzadeh (1994), Ratnasingham (1998), McHaney, Hightower andPearson (2002) and Somers, Nelson and Karimi (2003). Customer satisfaction is performed a vital role for the e-banking context (Chen et al, 2012;Al-Hawari, 2014).…”
Section: Customer Satisfaction In E-bankingmentioning
confidence: 99%
“…In fact, this model operationalizes customer satisfaction for e-banking as a multidimensional construct, which includes dimensions are content, accuracy, format, ease of use, timeliness and safety (See Figure 2). Notably, this model is rooted from user satisfaction literature, especially previous studies from Doll, Xia and Torkzadeh (1994), Ratnasingham (1998), McHaney, Hightower andPearson (2002) and Somers, Nelson and Karimi (2003). Customer satisfaction is performed a vital role for the e-banking context (Chen et al, 2012;Al-Hawari, 2014).…”
Section: Customer Satisfaction In E-bankingmentioning
confidence: 99%
“…They suggest that user satisfaction is a key predecessor to ERP systems' ultimate success. Furthermore, satisfaction with ERP system had been used as a surrogate measure of ERP success and a requisite for the realization of benefits of ERP systems (Somers et al, 2003). Garača (2011) applied TAM to a model of ERP acceptance and found that perceived ease of use and perceived usefulness demonstrated significant effects of satisfaction with ERP system, which in turn demonstrated a significant impact on ERP acceptance and use.…”
Section: Satisfactionmentioning
confidence: 99%
“…Thus, ERP informativeness can be defined as the extent to which an ERP system provides its users with the information they need to complete their job activities. As noted earlier, businesses implement ERP systems not only to replace the fragmented legacy systems dispersed throughout their organizational units, but also to consolidate all business data from disconnected databases into a central database to improve delivery of critical information to users, improve data consistency, and increases visibility of corporate data (Ram et al, 2013;Somers, Nelson, & Karimi, 2003). Based on the notion that the need for information drives peoples' use of a technology (Alajmi et al, 2016), the extent to which an ERP system can fulfill the information needs of its users is critical to the success of an ERP system.…”
Section: Informativenessmentioning
confidence: 99%
See 2 more Smart Citations